Megaptera novaeangliae - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Megaptera novaeangliae (Borowski, 1781). Gemein. Naturgesch. Thier., 2(1):21. TYPE LOCALITY: U.S.A., coast of New England. DISTRIBUTION: Worldwide, tropical to arctic waters. COMMENT: Includes nodosa; see Kellogg, 1932, Proc. Biol. Soc. Wash., 45: 148. PROTECTED STATUS: CITES - Appendix I and U.S. ESA - Endangered. ISIS NUMBER: 5301411007002001001. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Cetacea, pp. 290-304 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 303, DOI: 10.5281/zenodo.7352983